Pulmonary Embolism and Pregnancy—Challenges in Diagnostic and Therapeutic Decisions in High-Risk Patients - Hobohm, Lukas; Farmakis, Ioannis T.; Münzel, Thomas; Konstantinides, Stavros; Keller, Karsten (Frontiers in Cardiovascular Medicine, 2022)
Diagnosis of acute PE in pregnant women with haemodynamic instability is following the general integrated risk-adapted diagnostic algorithm and starts with bedside echocardiography to assess RV function. If RV dysfunction is identified, a prompt and immediate reperfusion without further imaging should be initiated. Although pregnancy is listed as a relative contraindication of systemic thrombolysis, in pregnant women with acute PE and haemodynamic instability thrombolysis must be considered. In those cases, other treatment strategies as surgical embolectomy or catheter-directed low-dose thromboylysis or percutaneous thrombectomy should be taken into consideration as well. A multidisciplinary team with experience of PE management in pregnancy should be consulted to reach consensus on the best treatment approach.